The Meaning of Education for Sustainable Development and Energy on the New East Timor Curricula - Capelo, Ana (Journal of Research in Educational Sciences, 2013)
In several countries, numerous citizens survive in problematic conditions, such as extreme poverty, hunger, disease and social conflicts, which may create many problems, e.g. pollution, deforestation, climate change and its consequences. To promote sustainable development considering social, economic and environmental dimensions, education in general, science education in particular, must focus on the development of skills and its contribution to responsible decision-making – essential to integrate education for sustainable development (ESD) principles and values. Curricular restructuration of general secondary education in East Timor intends to promote sustainability, e.g. to preserve and value of energy resources. The integration of issues relating to energy resources in the new curricular materials prepared within the restructuration of the 10th year of Biology and Chemistry, articulating the need to learn science with the inter-relationships promotion between science, technology and society (known by the STS acronym), by integrating ESD values and principles.